The EU Code of Practice on Disinformation: An Example of the Self-Regulatory Trend in International and European Law - Espaliú Berdud, Carlos (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Among the instruments that the EU has promoted in the fight against disinformation, the Code of Practice on Disinformation, which was drafted by the major online platforms in 2018 and was essentially self-regulatory in nature, stands out. After its implementation, some weaknesses were identified, which were addressed by drafting a new, strengthened version of the code in 2022. Although it responds to the same characteristics as the 2018 Code, its potential effectiveness is strengthened by being framed within a broader legal framework, in conjunction with the DSA among other instruments. Indeed, we believe that only a collective effort, both by private actors in this field, together with national and international public authorities, and following a multidisciplinary approach, guarantees the ability to oppose the monster of disinformation that terrorises contemporary societies. This is without forgetting respect for the essential freedoms of information and expression.